Best practices in doctoral retention: Mentoring - Judie L. Brill; Karen K. Balcanoff; Denise Land; Maurice Gogarty; Freda Turner (Laureate Education Inc, 2014)
The aim of this critical literature review is to outline best practices in doctoral retention and the successful approach of one university to improve graduation success by providing effective mentorship for faculty and students alike. The focus of this literature review is on distance learning relationships between faculty and doctoral students, regarding retention, persistence, and mentoring models. Key phrases and words used in the search and focusing on mentoring resulted in over 20,000 sources. The search was narrowed to include only doctoral study and mentoring. Research questions of interest were: Why do high attrition rates exist for doctoral students? What are the barriers to retention? What are the benefits of doctoral mentoring? What programs do institutions have in place to reduce attrition? The researchers found a key factor influencing doctoral student retention and success is effective faculty mentorship. In particular, the design of a mentoring and faculty training program to increase retention and provide for success after graduation is important. This research represents a key area of interest in the retention literature, as institutions continue to search for ways to better support students during their doctoral programs and post-graduation. DOI: 10.18870/hlrc.v4i2.186